PENGARUH UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING - Prasetya, Pria Juni; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
The purpose of this study was to determine the effect of firm size on earnings management through corporate social responsibility disclosure. Population in this study are all of manufacturing companies listed in Indonesia Stock Exchange 2012-2014 period. Number of samples 42 companies obtained by purposive sampling technique. Data Analysis used in this study is the path analysis. This study  found that firm size positive effect on corporate social responsibility disclosure. firm size and corporate social responsibility disclosure negative effect on earnings management. firm size significantly negative effect on earnings management through corporate social responsibility disclosure. This indicates corporate social responsibility disclosure able to mediate the relationship between firm size and earnings management.
Keywords: firm size, corporate social responsibility disclosure, and eranings management